CONSUMER’S ATTITUDES TOWARDS GREEN MARKETING PRODUCTS IN KANNUR DISTRICT - Sumesh P C (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The growing concern for the environment in the last few years has led to a large increase in the demand for eco-friendly items in India. Modern consumers are increasingly environmentally conscious and are ready to pay more for goods that protect the environment. Customers have different mind-sets when it comes to purchasing, and these attitudes are constantly changing due to the abundance of excellent options. Products are selected for a variety of reasons. In general, today's shopping process is very fast. Therefore, the objective of this study is to find out how much influence the attitudes of consumers of Kannur district have towards eco-friendly products. The study examines the relationship between factors that influence consumers' attitudes toward environmentally friendly products and identifies the price point at which they are most willing to cover the cost of environmentally friendly goods in the district.